Variabilidade do padrão de esterases e atividade da glutationa S-transferase em linhagens geográficas de Drosophila melanogaster e D. simulans resistentes e suscetíveis ao inseticida DDT - Valeriano, Emiliyn Kely Morón [UNESP] (2013)
D. melanogaster and D. simulans are sister species native to tropical Africa which diverged from a common ancestor about two Myr. These species have been compared in several traits, including morphology, physiology, sexual behavior, allozymes and other proteins, chromosomal inversions, nuclear and mitochondrial DNA, transposable elements, Wolbachia infection among others. However, studies in populations of South America, including Brazil, are scarce. The main objective of the study was to compare geographic strains of D. melanogaster and D. simulans from Brazil, Africa and France, for susceptibility to the insecticide DDT, the pattern of α and β esterases, especially in relation to the frequency of the polymorphism of esterase-6 in individuals phenotyped as resistant and susceptible, and the activity of glutathione-S-transferase . Both species showed a wide variability in LC50 values obtained. The highest values were observed in African strains of D. melanogaster and D. simulans, TANA (447.89 mg / mL), and TANA-4 (920 / mL). The Canton-S strain of D. melanogaster was the one with the lowest LC50 = 2.99 mg / mL. Comparing populations from the same location of both species the strains of D. melanogaster showed LC50 values larger than D. simulans, except FLO D. simulans strain had a LC50 (94.60) slightly higher than D. melanogaster (81.82). We analyzed two bands α-esterases, which we call α-1 and α-2, and the band α-2 was observed in 100% of all individuals analyzed in both species. The data show greater genetic variability for D. melanogaster for resistance to DDT, high resistance to African strains of both species, indicating that these populations continue to be selected by this or another insecticide, the lack of a cline for the F and S alleles in strains of both species, suggest that treatment with DDT may have selected individuals heterozygous for some strains, which may have masked the...